Pengaruh Performance Risk Dan Time-Loss Risk Terhadap Kepercayaan Dan Repurchase Intention Pada Live Shopping - Made Pradnyan Permana Usadi; I Putu Wahyu Dwinata JS; I Made Surya Prayoga; I Gede Rihayana; I Wayan Gede Antok Setiawan Jodi (Journal Research of Management, 2025)
Amid the rapid growth of live shopping as a digital marketing strategy, consumer risk perception has emerged as a critical concern. Product mismatches and wasted time during live broadcasts present serious challenges that undermine consumer trust and hinder repurchase intention. This study employs the Stimulus-organism-response (S-O-R) framework to examine how performance risk and time-loss risk—representing perceived risk stimuli—affect consumer trust (organism) in live shopping, ultimately influencing repurchase intention (response). A quantitative survey was conducted with 160 respondents who had previously engaged in live shopping. The data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that both performance risk and time-loss risk have a significant negative impact on trust, while trust significantly and positively influences repurchase intention. These results underscore the importance of managing risk perceptions to build consumer trust and foster repurchase intention in live shopping environments.